Ethnopedagogical Study: The Value of Local Wisdom in the Banjarmasin Floating Market as a Basis for Strengthening Citizenship Civic Disposition - Helda Yuliani (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2022)
Education is an absolute necessity that must be fulfilled throughout life. In addition to being faced with the development of technology and information, the world of education today is also faced with a very diverse social and cultural reality (multicultural). Thus, education inevitably must also respond and adapt to the culture of the surrounding community and transform these cultural values.The Indonesian nation consists of various ethnicities, cultures and local wisdom. Culture plays an important role in the education process. The values of local wisdom have a strategic role in the formation of national character and identity. Local wisdom is an identity or cultural personality of a nation that causes the nation to be able to absorb, even process culture that comes from outside / other nations into its own character and abilities. The values of local wisdom have a strategic role in the formation of national character and identity. Education developed by utilizing local wisdom will lead to the emergence of independent, disciplined, tolerant, responsible and creative attitudes. The Floating Market as a form of local wisdom of the Banjarmasin community can be used as a source of knowledge, values, character and character for the local community through an ethnopedagogic approach